The European Imperialism in West Coast Africa - GOUAD SEBA, Miloud (My University, 2020)
The period of nineteen century was special, where it took a new way as large expansions of colonialism policy, scholars called it the new imperialism. Colonial rules consist of direct military intervention, sending thousands colonials to settle and live there. Each European power such as: France, Britain, Germany, Portugal, Netherlands, and Belgium, etc. As a result of Berlin Conference (1884-1885), the King of Belgium Leopold II decided to target the Congo basin under the International Association of Congo, and the Congo Free State. Therefore, with its imperial tendencies, it intervened in Congo and exploited its people. This research aims to showcase a new form of imperial power called the New Imperialism applied on Congo, and it evaluates the different degrees of this new form of imperialism by using previous theories to help understand the Congolese experience with the Belgium imperial power in late nineteenth century until the death of the King of Belgium Leopold II in 1909. Based on the review of literature and previous theories related to the New Imperialism, a thorough analysis was executed to make sense of the term to pave the way to introduce and compare those theories to the Congo case. The analysis has demonstrated that New Imperialism in Congo was merely a façade that supposedly aimed to develop, civilize and Christianize, but in reality Leopold II considered Congo and its people as private property.
Case Study: Congo (1880-1909)
Keywords: Imperialism; New Imperialism; Congo basin; Leopold II; International Association of Congo